Performance monitoring of PPVC connectors - Tan, Fook Aik (Nanyang Technological University, 2021)
With the recent game changing technologies, Prefinished Prefabricated Volumetric Construction (PPVC) has become the default method for high-rise construction. The use of PPVC could improve the productivity on-site and at the same time, reduce the project duration and cost. As this approach is relatively new, there is no design code specifically on this PPVC system.